Public Policy on Countering Online Gambling in Indonesia - Yusup Permana, Deni; Gunawan, Moh. Sigit; Widyani, Retno (ann4publisher@gmail.com, 2024)
Public policy to combat online gambling in Indonesia involves various efforts from various sectors, including the government, police, and legal institutions. Here are some important points of the policy: Cooperation with the Police. The government works with the police to eradicate online gambling applications in the community. This policy involves actions such as blocking content and applications that have gambling elements, as well as legal action against online gambling perpetrators. Laws and Legal Policies: The Government has made laws that regulate online gambling, such as Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. This policy includes legal action against online gamblers, including serious threats to perpetrators who deliberately distribute electronic information that has gambling content[2][4]. Handling Negative Content: Policies in the downstream sector involve handling negative content by blocking content and applications with gambling elements. The goal is to reduce the development of online gambling in society. Penal and Non-Penal Handling, Online gambling countermeasures are carried out penal and non-penal. Penal countermeasures involve legal actions such as imprisonment and fines, while non-penal countermeasures involve prevention and community empowerment efforts[3]. Future Policy: to anticipate gambling crimes in the future, the government can use penal means. Some of the alternative formulation policies that will be revamped include the addition of additional criminal penalties, such as the revocation of the right to practice the profession for makers who commit gambling crimes in carrying out their profession. The government seeks to prevent and follow up on online gambling crimes with these various policies.